Gauge Theories in Particle Physics: A Practical Introduction, Volume 2: Non-Abelian Gauge Theories QCD and The Electroweak Theory, Fourth Edition - Aitchison, Ian J R (Taylor & Francis, 2013)
Volume 2 of this revised and updated edition provides an accessible and practical introduction to the two non-Abelian quantum gauge field theories of the Standard Model of particle physics: quantum chromodynamics (QCD) and the Glashow-Salam-Weinberg (GSW) electroweak theory.This volume covers much of the experimental progress made in the last ten y